Organization of anti-epidemiological work and sanitary education in the Saratov region during the Great Patriotic War - Zavialov A. I., Iakupov I. A. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the article is devoted to the organization and implementation of preventive measures of infectious diseases and dissemination of medical knowledge among the population of the Saratov region during the Great Patriotic War due to the high migration of the population from other regions of the country.
Keywords: Великая Отечественная война; Great Patriotic War; Саратовская область; Saratov region; санитарное просвещение; sanitary education